Convergent origin and accelerated evolution of vesicle-associated RhoGAP proteins in two unrelated parasitoid wasps - Colinet, Dominique; Cavigliasso, Fanny; Leobold, Matthieu; Pichon, Apolline; Urbach, Serge; Cazes, Dominique; Poullet, Marine; Belghazi, Maya; Volkoff, Anne-Nathalie; Drezen, Jean-Michel; Gatti, Jean-Luc; Poirié, Marylène (Peer Community Journal)

(untitled)
Animal venoms and other protein-based secretions that perform a variety of functions, from predation to defense, are highly complex cocktails of bioactive compounds. Gene duplication, accompanied by modification of the expression and/or function of one of the duplicates under the action of positive selection, followed by further duplication to produce multigene families of toxins is a well-documented process in venomous animals. This evolutionary model has been less described in parasitoid wasps, which use maternal fluids, including venom, to protect their eggs from encapsulation by the host immune system. Here, we evidence the convergent recruitment and accelerated evolution of two multigene families of RhoGAPs presumably involved in virulence in two unrelated parasitoid wasp species, Leptopilina boulardi (Figitidae) and Venturia canescens (Icheumonidae). In both species, these RhoGAPs are associated with vesicles that act as transport systems to deliver virulence factors, but are produced in different tissues: the venom gland in Leptopilina sp. and the ovarian calyx in V. canescens. We show that the gene encoding the cellular RacGAP1 is at the origin of the virulent RhoGAP families found in Leptopilina sp. and V. canescens. We also show that both RhoGAP families have undergone evolution under positive selection and that almost all of these RhoGAPs lost their GAP activity and GTPase binding ability due to substitutions in key amino acids. These results suggest an accelerated evolution and functional diversification of these vesicle-associated RhoGAPs in the two phylogenetically distant parasitoid species. The potential new function(s) and the exact mechanism of action of these proteins in host cells remain to be elucidated.